ROLE OF NANOPARTICLES IN THE EFFICACY OF ANTIBIOTICS - Ukashah, Muhammad; Ijaz, Bareera; Riaz, Muhammad A; Javed, Muhammad K (Global Journal of Medical and Health Science, 2023)
Now a day, the reason of greater mortality rate is due to bacterial diseases. The cure of bacterial diseases is the use of antibiotics but there is a problem that bacteria have become multidrug resistant and so antibiotics can’t be used for treating bacterial diseases. A great revolution in this aspect is the use of nanoparticles. Nanoparticles can be made from different metals like gold, copper, zinc etc. The mode of action of nanoparticles is that they enter into the cell membrane of pathogen and affect their molecular pathways. Nanoparticles are used in combination with different drugs. The nanoparticles which have been extensively studied are silver nanoparticles. Experiments were performed of check the efficiency of silver nanoparticles in gram positive and gram negative bacteria. Silver nanoparticles were not used with the combination of any drug. Nanoparticles are stable for long time as they are surrounded by capping layers because of which they are stable for long time. Another important function of these capping layers is that they are also providing active surface area for the interaction with other biological components. Shortly, we can say that nanoparticles can be used as an alternative to antibiotics and they can serve us in better way.